Methyltrimethyltridecylchromans (MTTCs) in Mature Crude Oils: Implications for Oil Family Classification and Palaeoenvironmental Diagnosis - Youjun Tang; Mengyue Han; Xiaoyong Yang; Ke Liu; Lian Chen; Yahao Mei; Yulu Han; Tianwu Xu; Chengfu Zhang (Journal of Marine Science and Engineering)
Methyltrimethyltridecylchromans (MTTCs), a class of oxygen-containing aromatic derivatives, have been used as indicators of paleosalinity in source rocks and crude oils. However, the reliability of these compounds as indicators in mature organic matter remains unclear, hindering a definitive assessment of their significance for oil–oil or oil–source rock correlation. In this study, a suite of mature oils and associated source rocks from the Paleogene Shahejie (E2s) Formation in the Machang area, Dongpu Depression, Bohai Bay Basin, were analyzed. The distribution of bulk compositions and biomarkers in the oils and source rock extracts suggests a genetic relationship, indicating that the oils were derived from similar organic matter (predominantly algae and aquatic macrophytes) and depositional environments (low salinity), with comparable maturity levels (within the middle oil window). The β/γ-MTTC ratio, a proposed maturity indicator, appears unreliable in mature organic matter, as evidenced by its poor correlation with established maturity proxies (e.g., C29 24-ethylcholestanes αββ/(ααα + αββ)) in the studied samples. In contrast, MTTC-based salinity paraments (α/δ, α/γ, MTTCI, and the cross-plot of MTTCI versus Pr/Ph) consistently reflect a low-salinity depositional environment for these crude oils and source rocks, except in the ternary diagram of relative alkylation abundances. These findings suggest that MTTC-derived paleosalinity indicators may serve as effective tools for oil–oil or oil–source rock correlation within the middle oil window. This study provides evidence supporting the broader applicability of MTTC-based proxies for paleosalinity reconstruction and correlation studies, particularly in mature organic matter under geological conditions. The results also offer insights for regional petroleum exploration in saline lacustrine basins.